THE EFFECT OF REWARDS AND PENALS AND TRAINING ON EMPLOYEE PERFORMANCE THROUGH ORGANIZATIONAL COMMITMENTS AS INTERVENING VARIABLES - Abadi Sanosra; Toni Herlambang; Dina Triya Yuliasari (STIE Mandala Jember, 2022)
The purpose of this study was to determine directly or indirectly the effect of rewards andpunishments and training on employee performance through organizational commitment as anintervening variable at the Bondowoso Regency Environmental and Transportation Agency. Thenumber of samples in this study was 114. The analytical technique used was the StructuralEquation Model (SEM) using WarpPLS 5.0. The results of data analysis show that the variablerewards and punishments have a significant effect on organizational commitment, training has asignificant effect on organizational commitment, rewards and punishments have a significanteffect on employee performance, training has a significant effect on employee performance,organizational commitment has a significant effect on employee performance.Keywords: Rewards and Punishments, Training, Commitment and Performance